Physical rehabilitation of children and adolescents with oncohematological pathology after hematopoietic stem cell transplantation - A. A. Potapchuk; F. V. Terentyev (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Introduction. This article is devoted to the description of the method of physical rehabilitation of children and adolescents of 12–17 years old after hematopoietic stem cell transplantation and the analysis of the effectiveness of this method on the indicators of physical, emotional state and quality of life assessment.The objective of the study was to scientifically substantiate the effectiveness of the method of physical rehabilitation of adolescents who underwent hematopoietic stem cell transplantation.Methods and materials. The experiment involved 40 adolescents with oncopathology who were admitted for treatment at R.M. Memorial Research Institute for Pediatric Oncology, Hematology and Transplantation, of which 16 girls and 24 boys aged 12 to 17 years: experimental group 1 (EG1 ) – 20 patients and experimental group 2 (EG2) – 20 patients. In EG2, classes were held 3 times a week together with an instructor-methodologist of exercise therapy and were taught independently according to a specially developed methodological and video material with filling in a self-control diary.Results. The application of the developed method of physical rehabilitation of adolescents contributes to: optimizing the physical condition: indicators of the life index improved by 5.5 %; power index by 28.9 %; the level of aerobic endurance by 18.3 %; carpal dynamometry of the right hand by 6.5 %, carpal dynamometry of the left hand by 5.2 %; indicators of vital capacity of the lungs improved by 6.5 %; the time of passage of the straight line by 25.7 %, the improvement of the psycho-emotional state – indicators of anxiety and depressive states decreased by 22.3 %, the improvement of the quality of life: physical, emotional, social functioning improved by 7.4 %; pain and soreness, fatigue and sleep, nausea, anxiety, nutrition, thinking, communication improved by 9.3 %.Conclusion. Thus, the presented method of physical rehabilitation has shown its effectiveness.